2019
DOI: 10.3390/nu11102347
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Folic Acid Supplementation during Pregnancy: A Multicenter Study in Vietnam

Abstract: Periconceptional folic acid (FA) supplementation is recommended to prevent neural tube defects (NTDs), but little information is known about its use in Vietnam. It is important that FA supplements start to be taken when planning a pregnancy and continued through the first trimester to prevent NTDs, as the neural tube closes in the first month of pregnancy. However, FA supplementation in Vietnam is usually recommended to commence from the first antenatal visit, which is usually at 16 weeks, and very few women t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
3
6
0
1
Order By: Relevance
“…Most pregnant women who purchase FA supplements or compound vitamins containing FA for themselves have sufficient financial resources through their own employment. Consistent with a previous study [ 39 ], we found that pregnant women who had a planned pregnancy had a higher likelihood of taking FA at the appropriate time (adjusted OR = 6.18, 95% CI 4.01–9.53). Our findings showed that pregnancy planning was positively associated with the consumption of FA supplements during the periconception period.…”
Section: Discussionsupporting
confidence: 91%
“…Most pregnant women who purchase FA supplements or compound vitamins containing FA for themselves have sufficient financial resources through their own employment. Consistent with a previous study [ 39 ], we found that pregnant women who had a planned pregnancy had a higher likelihood of taking FA at the appropriate time (adjusted OR = 6.18, 95% CI 4.01–9.53). Our findings showed that pregnancy planning was positively associated with the consumption of FA supplements during the periconception period.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it should be noticed that the questionnaire used in this study mentioned only physical exercise but not domestic work or work activities. Additionally, the rates of taking iron and folic acid were higher compared to a previous study conducted in Vietnam (25.8%) [48]. This result was similar to that reported in China (66.7%) [49], but higher than that of Japan (20.5%) [50], and Korea (10.5%) [51].…”
Section: Discussionsupporting
confidence: 82%
“…Though, other global countries have limited knowledge regarding supplementation of FA during pregnancy. [ 36 37 38 39 ]…”
Section: Discussionmentioning
confidence: 99%